Effect of Weight-Reduction in Obese Mice Lacking Toll-Like Receptor 5 and C57BL/6 Mice Fed a Low-Fat Diet - Shao-Chun Wu; Cheng-Shyuan Rau; Tsu-Hsiang Lu; Siou-Ling Tzeng; Yi-Chan Wu; Chia-Jung Wu; Chia-Wei Lin; Ching-Hua Hsieh (Hindawi Limited, 2015)
Background. This study aims to investigate the effect of feeding low-fat diet (LFD) to diet-induced obesity (DIO) mice lacking TLR5 (TLR5−/−), which have a tendency to develop glucose intolerance with increased adiposity, compared to that in C57BL/6 mice. Results. TLR5−/− and C57BL/6 male mice were divided into three subgroups: (1) control, mice were fed a standard AIN-76A (fat: 11.5 kcal%) diet for 12 weeks; (2) DIO, mice were fed a 58 kcal% high-fat diet (HFD) for 12 weeks; and (3) diet, mice were fed a HFD for 8 weeks to induce obesity and then switched to a 10.5 kcal% LFD for 4 weeks. The glucose intolerance in DIO TLR5−/− mice was more significant than that in DIO C57BL/6 mice and was not attenuated by a switch to the LFD. Weight-reduction with LFD had significantly decreased the epididymal fat mass in C57BL/6 mice but not in TLR5−/− mice. In addition, the LFD-fed TLR5−/− mice showed significantly higher expression of ghrelin in the serum and resistin in the epididymal fat than that in C57BL/6 mice. Conclusions. This study demonstrated that TLR5 gene knockout impairs some effects of weight-reduction in DIO.